Job satisfaction among anaesthesiologists working at teaching and tertiary care hospitals of Lahore: Job satisfaction among anaesthesiologists working at teaching and tertiary care hospitals of Lahore - Javed, Khalid; Ishrat, Zahra; Chaudhary, Tahir Mahmood (Journal of Fatima Jinnah Medical University, 2020)
Background: Anaesthesiology is perioperative medicine that also encompasses intensive and critical care and pain management. The breadth of the profession has dramatically expanded in the last decade. Anesthesiology not only requires a considerable depth of knowledge but also demands experience, fine skills, vigilance ,dedication and commitment to the job, which makes it stressful and increases the risk of burnouts and job dissatisfaction among anesthesiologists. The purpose of this study was to assess job satisfaction among anesthesiologists working at teaching and tertiary care hospitals of Lahore and to identify factors responsible for job related stress and dissatisfaction. Patients and Methods: A cross-sectional study, questionnaire based. The study was conducted after approval from the Local Ethical Committee. Total 171 anesthethesia consultants, senior registrars, registrars and medical officers working at teaching and tertiary care hospitals of Lahore participated in this study. A questionnaire was designed to collect informations regarding job satisfaction, private practice , professional income, public awareness of the specialty, identification of stressors, working relationship with surgeons , working environment and other elements associated with job dissatisfaction. There were 23 questions that had to be answered in either yes or no and data was presented as frequencies and percentages.